According to Hastie's paper, the elastic net has two equivalent formulations:

$$\hat{\beta} = \underset{\beta}{\operatorname{argmin}} \left\{ \sum_{i=1}^N\left(y_i-\sum_{j=1}^p x_{ij} \beta_j\right)^2 + \lambda_1 \sum_{j=1}^p |\beta_j|+ \lambda_2 \sum_{j=1}^p \beta_j^2 \right\}$$


$$\hat{\beta} = \underset{\beta}{\operatorname{argmin}} \left\{ \sum_{i=1}^N\left(y_i - \sum_{j=1}^p x_{ij} \beta_j\right)^2\right\} \;\text{ s.t. } \;(1-\alpha)\sum_{j=1}^p |\beta_j| + \alpha\sum_{j=1}^p \beta_j^2 \leq t$$

where $\alpha = \frac{\lambda_2}{\lambda_1 + \lambda_2}$

My question is how to prove this equivalence formally. Ridge regression and the lasso also have these two possible formulations, but I could not find any reference where this equivalence is proven. A similar question I found in CrossValidated is this one

Lagrangian relaxation in the context of ridge regression

but I'm unable to understand Tristan's explanation. I have some understanding of Lagrange optimization theory, and I guess the answer is around those lines, but since all the papers treat the equivalence as obvious I would like to find a proper reference where this is explicitly demonstrated.

  • $\begingroup$ This question on just Ridge Regression is highly related. $\endgroup$ Commented Nov 10, 2018 at 7:06

1 Answer 1


Starting from $$\hat{\beta} = \arg \min_\beta \|X\beta - y\|_2^2 \text{ s.t. } (1-\alpha)\|\beta\|_1 + \alpha\|\beta\|_2^2 \leq t,$$ we can write the dual Lagragian formulation of this optimization problem as $$ \begin{array}{rcl} L(\beta,\alpha,\lambda) & = & \|X\beta - y\|_2^2 + \lambda \left( (1-\alpha)\|\beta\|_1 + \alpha\|\beta\|_2^2 - t\right) \\ & = & \|X\beta - y\|_2^2 + \lambda (1-\alpha)\|\beta\|_1 + \lambda\alpha\|\beta\|_2^2 - \lambda t, \end{array} $$ and we see that this indeed looks like the first problem that you wrote, with parameters $\lambda_1=\lambda (1-\alpha)$ and $\lambda_2=\lambda \alpha$, which leads to the expression of the "elastic" parameter: $$\alpha = \frac{\lambda_2}{\lambda_1+\lambda_2}.$$ That being said, to go from this point to Zou and Hastie's assertion that both problems are equivalent, I admit that I miss a step or two...

  • $\begingroup$ I know how to do the equivalence between ridge regression formulations (since it is differenciable) but I'm wondering if it would be any easier to consider only the $l_1$ norm instead of the elastic net penalty? $\endgroup$
    – skd
    Commented Sep 3, 2013 at 15:00

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.